Perbandingan Desain Lug Groove dan Dovetail pada Bata interlock Terhadap Kuat Tekan - Augdrie, May Haidar; Rochmah, Nurul (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The main problem in conventional wall construction lies in the limited compressive strength of clay bricks and the low efficiency of installation, both of which negatively affect structural performance and overall construction productivity. Conventional masonry also exhibits high variability in quality, making it less reliable for modern construction demands. Although interlocking concrete bricks have been introduced as an alternative solution to improve installation efficiency, the influence of interlocking geometric variations on compressive strength has not been examined comprehensively, particularly for Lug Groove and Dovetail configurations. This study aims to analyze the effect of these two interlocking geometries on the compressive strength of concrete bricks and to evaluate their conformity with the Indonesian standard SNI 03-0349-1989. The research was conducted using an experimental quantitative approach in a laboratory setting. Concrete brick samples were cast using wooden molds with two different interlocking geometries, namely Lug Groove and Dovetail. All specimens underwent a 7-day curing process prior to testing with a Compression Testing Machine (CTM). The maximum load sustained by each specimen was recorded and used to calculate compressive strength following the SNI formula, and the values were then converted into kg/cm² units. The results indicate that both interlock types fall into the solid concrete brick quality class II according to SNI. The average compressive strength of Lug Groove bricks was 43.99 kg/cm², while the Dovetail type reached 44.88 kg/cm². The difference between the two designs is relatively small, suggesting that geometric variation has only a limited effect on compressive strength. Nevertheless, both designs exhibit satisfactory mechanical performance and meet technical quality standards, making them suitable alternatives for efficient wall construction.